Climate tipping points and their potential impact on drinking water supply planning and management in Europe - Peter van Thienen; Herbert ter Maat; Sija Stofberg (Cambridge Prisms: Water)
The current generation of climate models has proven very helpful in understanding and projecting anthropogenic climate change but has also shown to be insufficient for studying the interactions of tipping elements and their impact on overall climate stability. As a consequence, tipping elements are mostly absent from climate projections that are commonly used by the drinking water industry to test the resilience of their systems. There is, however, mounting evidence for the existence and potential (possibly even imminent) activation of some of these tipping elements. The drinking water sector is, by necessity, slow-moving as its infrastructure is meant to operate for many decades and in practice often does so even longer. The time scales of possible changes associated with tipping element activations may, however, be much shorter. We provide a review of the current understanding of climate tipping elements and present a simple model that investigates potential magnitudes and time scales of rapid climate change associated with tipping element activations. We study the potential consequences for drinking water supply systems, focusing on Europe, and argue that given the associated deep uncertainty and far-reaching consequences, it is essential to include tipping scenarios in the decision-making processes in the drinking water sector.